Pengaruh Persepsi E-Commerce, Modal Usaha, dan Penggunaan Sistem Informasi Akuntansi Terhadap Keputusan Berwirausaha di Pandemi Covid-19 - Eva Risqita Listya Sari; Dyah Pravitasari (Politeknik Ganesha Medan, 2022)
Entrepreneurship among students is mushrooming. This is because students' thinking has changed. Those who have not done entrepreneurship because they have not realized the ability and intention to organize efforts to realize the dream of becoming a successful entrepreneur. This research has the aim of to analyze influence of e-commerce perception, venture capital and the use of accounting information systems in entrepreneurship decision-making in the Covid-19 pandemic. The population to be studied is all students of the Majoring in Sharia Accounting class of 2018, Sayyid Ali Rahmatullah Tulungagung State Islamic University. The study sample was 70 students selected by random sampling method. This research uses quantitative methods. The type of research conducted is associative. The method of data collection used is to distribute questionnaires. The results of this study showed that the perception of e-com merce and the use of accountin g infor mation systems had a pos itive and sign ificant effect on entre preneurship decisions in the Covid-19 pandemic, venture capital had no effect and was insignificant to entrepreneurship decisions in the Covid-19 pandemic. If tested simultaneously, it shows that the three variables, namely perceptions of electronic commerce, venture capital and the utilization of accountancy information systems, affect entrepreneurship decisions at Covid-19 pandemic.